FENOMENA DIGITALISASI DAN PENGARUHNYA TERHADAP KEYAKINAN DAN PRAKTIK AGAMA KRISTEN - Mase, Boyes Agustina; Natalia (Jurnal Teologi RAI, 2024)
This research discusses current development breakthroughs that are very important for every individual. How each individual can break through the development of the times with positive things is not only felt by every individual in the religious environment, the development of the times, namely in the world of digitalization, is something that must be penetrated in Christianity, how Christianity can enter and continue to exist in carrying out evangelization and carrying out Christ's mission in this world by utilizing digitalization technology which has become a phenomenon for every individual. Therefore, our role in the digital world as believers must be to bring blessings and carry out missions in the practice of Christian religious beliefs in today's digital world.